2011
DOI: 10.1016/j.electstud.2010.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Raising the tone? The impact of ‘positive’ and ‘negative’ campaigning on voting in the 2007 Scottish Parliament election

Abstract: Most research on campaign effects in British elections has focussed on exposure to the campaign. Far less attention has been given to how the campaign is perceived, although American research on the effects of negative campaigning suggests that this is a potentially important area. The article investigates the extent to which vote choices in the 2007 Scottish Parliament election were affected by perceptions of the parties' campaigns as 'positive' or 'negative'. Partisanship and increased exposure to a party's … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 24 publications
2
33
0
Order By: Relevance
“…This observation is particularly relevant for party research since parties would want to activate positive emotions among their base, considering the backfiring effects of negative campaigning that previous research has identified (Banda and Windett ; Dowling and Wichowsky ; Pattie et al. ).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This observation is particularly relevant for party research since parties would want to activate positive emotions among their base, considering the backfiring effects of negative campaigning that previous research has identified (Banda and Windett ; Dowling and Wichowsky ; Pattie et al. ).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Morality does not have to entail negative emotions, and there is much reason to explore its positive emotional consequences (see also Haidt 2003a;Tangney, Stuewig, and Mashek 2007). This observation is particularly relevant for party research since parties would want to activate positive emotions among their base, considering the backfiring effects of negative campaigning that previous research has identified (Banda and Windett 2016;Dowling and Wichowsky 2015;Pattie et al 2011).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Hence, actors’ differential use of characterizations may ultimately derive from a strategic decision to adopt a negative or positive campaign tone in a policy conflict (Schlaufer, , p. 107). There is a large body of extant research on messaging in electoral campaigns (Fridkin & Kenney, ; Pattie, Denver, Johns, & Mitchell, ), but actors in ongoing policy disputes are equally likely to deliberately shape their narratives to maximize the impact. I will therefore use the notion of negative and positive campaign tone as shorthand for the relative strength of the devil or angel shift.…”
Section: The Narrative Policy Framework (Npf)mentioning
confidence: 99%
“…Even though this campaigning strategy prospectively contributed to the success of the Republican candidate (Donald Trump), there is evidence that negative campaigning is risky and might backfire, leading to undesired effects (e.g. by making a candidate less likeable, see [PDJM11]). As part of our study, we examined cases of negative campaigning found in our data-set (including the spread of misinformation and rumors) and the effects on the candidates' followers.…”
Section: Rq11: What Are the Temporal Characteristics Of Each Candidamentioning
confidence: 99%